20 years of Hepcidin: how far we have come - Colucci, Silvia; Marques, Oriana; Altamura, Sandro (Seminars in hematology, 2021)
Twenty years ago the discovery of hepcidin deeply changed our understanding of the regulation of systemic iron homeostasis. It is now clear that hepcidin orchestrates systemic iron levels by controlling the amount of iron exported into the bloodstream through ferroportin. Hepcidin expression is increased in situations where systemic iron levels should be reduced, such as in iron overload and infection. Conversely, hepcidin is repressed during iron deficiency, hypoxia or expanded erythropoiesis, to increase systemic iron availability and sustain erythropoiesis. In this review, we will focus on molecular mechanisms of hepcidin regulation and on the pathological consequences of their disruption.
Gesehen am 01.04.2022